Understanding consumer behaviour regarding sustainability in the food sector:The role of meat reduction and protein alternatives. - Ford, Hannah Lily (2024)
The need to better understand and shift current consumer behaviour towards more sustainable food consumption habits is imperative for achieving a more food secure future. Increasingly, consumers are encouraged to reduce consumption of animal-sourced protein and transition towards a wider array of protein sources to alleviate associated environmental pressures and to address public health issues. Yet, the success of a protein transition is partly underpinned by consumer acceptance towards alternative products and changes to consumption habits. Considering the multifaceted nature of sustainability and the complexity of food choice behaviour, it is important to target and explore the influence of certain variables on consumer behaviour to inform behavioural change strategies.